MINDFUL LEARNING: A HYBRID SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Gusmawati; Ad Dailamay Wartindya Pradana Saputra, Fairus; Yayuk, Erna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to present a systematic literature review and bibliometric analysis on the development of Mindful Learning research within the educational context. Using the PRISMA method and the Scopus database, 44 relevant articles were selected from a total of 1,647 documents for in-depth analysis. The study focuses on three key research questions: the sustainability and relevance of Mindful Learning as a scientific topic (RQ1), the allocation of current research resources including publications, collaborations, and funding (RQ2), and the theoretical and practical implications of recent findings (RQ3). The results indicate that Mindful Learning remains a relevant and evolving area of global research, particularly since 2010. The United States, Taiwan, and China are the leading countries in terms of publications, while social sciences and psychology are the dominant disciplines. Keyword mapping further reveals strong connections between Mindful Learning and related concepts such as empathy, emotional regulation, and psychological well-being. The findings suggest that Mindful Learning holds significant potential to be integrated into broader educational practices. Additionally, the field offers ample opportunities for interdisciplinary and cross-cultural research. This study provides valuable insights for educators, researchers, and policymakers in designing more reflective, adaptive, and student-centered learning approaches that prioritize well-being alongside academic performance.